Ribosomal protein mutation suppresses gonadal leader cell migration defects in mig-17/ADAMTS mutants in Caenorhabditis elegans - Hon-Song Kim; Kaito Mitsuzumi; Shohei Kondo; Rie Yamaoka; Shinji Ihara; Hiroshi Otsuka; Chizu Yoshikata; Yukihiko Kubota; Takumi Tomohiro; Toshinobu Fujiwara; Kenji Kimura; Fumio Motegi; et al. (Scientific Reports)
Abstract The migration of gonadal distal tip cells (DTCs) in Caenorhabditis elegans serves as an excellent model for studying the migration of epithelial tubes during organogenesis. Mutations in the mig-17/ADAMTS gene cause misdirected DTC migration during gonad formation, resulting in deformed gonad arms. An amino acid substitution in RPL-20, the ortholog of mammalian RPL18a/eL20, a component of the 60 S ribosomal large subunit, exhibited a slow-growth phenotype and strongly suppressed the mig-17 gonadal defects. Slow-growing mutations clk-1 and clk-2 also suppressed mig-17. Intestine-specific overexpression of mutant RPL-20 protein resulted in a slow-growth phenotype and suppressed the mig-17 gonadal defects, but these effects were much weaker when wild-type RPL-20 was overexpressed, suggesting that the mutant RPL-20 protein acquired a novel function. Analysis of ribosome profiles revealed reduced biogenesis of the 60 S subunit, leading to a reduction of 80 S ribosomes in the rpl-20 mutant. These results suggest that DTC migration defects in mig-17/ADAMTS mutants can be partly suppressed by growth retardation caused by the rpl-20 mutation. While defective ribosome biogenesis may contribute to the observed growth retardation, further investigation is needed to clarify the molecular basis of this phenomenon.